Time-Dependent Secretion of IFN-γ, TNF-α, Perforin, and Granzyme-B in CTL-Conditioned Medium from Colorectal Cancer Patient - Sugeng Ibrahim; Agung Putra; Nurul Hidayah; Ahmed Faheem Khan; Dendi Krisna Nugraha (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2025)
Background: Cytotoxic T lymphocytes (CTLs) are key effectors of adaptive immunity, exerting their functions through the release of pro-inflammatory cytokines and cytotoxic molecules. Conditioned medium (CM) derived from CTLs has emerged as a potential cell-free immunotherapeutic strategy; however, the temporal dynamics of its secreted mediators remain poorly defined. Methods: Human CTLs were isolated, activated, and cultured in vitro. CM was harvested at defined intervals (days 5, 10, and 15). Concentrations of interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), perforin, and granzyme-B were quantified by enzyme-linked immunosorbent assay (ELISA). Temporal secretion profiles were evaluated using ANOVA with post-hoc analysis. Results: IFN-γ and TNF-α exhibited peak secretion at day 5, followed by a decline at later time points. In contrast, perforin and granzyme-B increased progressively, reaching maximal levels at day 15. All four mediators demonstrated significant time-dependent variation (p < 0.05). Conclusion: CTL-derived CM displays distinct time-dependent secretion patterns, with cytokines predominating during early activation and cytotoxic molecules dominating later phases. These findings underscore the importance of optimizing CM collection timing to maximize its immunomodulatory and therapeutic potential, and provide a rationale for further translational development of CTL-CM in immunotherapy.